A target-responsive liposome activated by catalytic hairpin assembly enables highly sensitive detection of tuberculosis-related cytokine. Issue 38 (26th April 2018) - Cui, Haiyan; Bo, Bing; Ma, Jun; Tang, Yingying; Zhao, Jing; Xiao, Heping
Abstract : A method for the highly sensitive detection of tuberculosis-related cytokine is developed by using a target-responsive liposome activated by catalytic hairpin assembly. Abstract : Here, we propose a new fluorescence method to detect tuberculosis-related cytokine by using a target-responsive liposome activated by catalytic hairpin assembly. The method combines a DNA self-assembly based amplification process with a liposome-based signal amplification process, therefore offering a very high sensitivity.